Analisis Kepuasan Konsumen Terhadap Peningkatan Volume Penjualan Sepeda Motor Honda pada PT. Nusantara Surya Sakti Perbaungan - Muhammad Idris (Institute of Computer Science (IOCS), 2019)
The sample in this study was taken from the population that is the number of consumers as much as 25% of 124 people, 31 people. From the results of the research that the author did, it can be concluded that: the value of product quality (X1) is 5.538 while the table with α = 5% and dk = 30 is t (0.025: 30) = 2.045 (tcount> t table). Thus H0 is rejected and H1 is accepted which means product quality has a significant effect on sales volume at PT. Nusantara Surya Sakti Perbaungan, tcount value of service quality has a significant effect on sales volume at PT. Nusantara Surya Sakti Perbaungan value of service quality (X2) is 2.823 while the table with α = 5% and dk = 30 is t (0.025: 30) = 2.045 (tcount> t table). Thus H0 is rejected and H1 is accepted, which means that service quality has a significant effect on sales volume at PT. Nusantara Surya Sakti The comparison of the emotional tcount (X3) is -0.484 while the table with α = 5% and dk = 30 is t (0.025: 30) = 2.045 (tcount <ttable). Thus H0 is accepted and H1 is rejected, which means emotional does not have a significant effect on sales volume at PT. Nusantara Surya Sakti Perbaungan value of Fcount is 11.739 while Ftable with α = 5% is F0.05; (k) (n-k-1) = 2.92 (Fcount> Ftable). Thus H0 is accepted and H1 is accepted which means product quality, waiter and emotional quality simultaneously has a significant effect on sales volume at PT. Nusantara Surya Sakti Perbaungan, the value of the multiple correlation coefficient is 0.924 that advertising, promotion, personal selling and publicity have a strong relationship with increasing sales volume at PT. Nusantara Surya Sakti Perbaungan and its determinant coefficient value from the calculation result is 0.566 which means that the sales volume can be explained by the diversity of product quality, service quality and emotional variables of 56.6%.